Efecto de sustratos organicos en el desarrollo de melón en condiciones de invernadero - Ramon Pacheco, Omar Lenin (Machala : Universidad Técnica de Machala, 2024)
The present study evaluated the effect of different organic substrates on the growth and development of melon (Cucumis melo L.) in a controlled environment. Five treatments were analysed, including a control, and key variables such as plant height, number of leaves and number of flowers were measured.The results showed that treatments consisting of clayey soil, balsa sawdust, dried cocoa and guabo leaves, plus biochar, significantly improved melon growth and development compared to the control. Treatment T2, involving the application of two litres of biochar, exhibited the most pronounced efficacy in enhancing plant height and floral abundance.At the 45-day stage after transplantation, T2 attained an average height of 246.7 cm and an average of 63 flowers, a substantial increase compared to the control (T5), which only reached an average height of 136.5 cm and 23 flowers. Treatment T4 (4 litres of biochar) demonstrated the highest number of leaves, with an average of 28 leaves per plant 30 days after transplanting, in comparison to the control, which had an average of 17 leaves.Furthermore, treatments T3 and T4 proved to be effective, with average heights of 245.8 cm and 240.9 cm, respectively, and a substantial number of flowers and leaves. In conclusion, the use of organic substrates is a viable alternative to optimise melon cultivation in greenhouses, promoting healthy and sustainable growth
En la investigación se evaluaron diferentes sustratos orgánicos y su efecto en el crecimiento y desarrollo del melón (Cucumis melo L.) en un entorno controlado. Se analizaron cinco tratamientos, incluyendo un testigo, midiendo variables clave como la altura de la planta, el número de hojas y el número de flores. Los resultados mostraron que los tratamientos conformados por tierra arcillosa, aserrín de balsa, hojas secas de cacao y guabo, más biochar, mejoraron significativamente el crecimiento y desarrollo del melón en comparación con el testigo. En particular, el tratamiento T2 que estuvo conformado por dos litro de biochar, resultó ser el más efectivo en términos de altura de planta y número de flores. A los 45 días después del trasplante, T2 alcanzó una altura promedio de 246.7 cm y un número promedio de 63 flores, destacándose significativamente sobre el testigo (T5), que solo alcanzó una altura promedio de 136.5 cm y 23 flores. El tratamiento T4 (4 litros de biochar) mostró el mayor número de hojas, con un promedio de 28 hojas por planta a los 30 días después del trasplante, en comparación con el testigo que tuvo un promedio de 17 hojas. Además, los tratamientos T3 y T4 también demostraron ser efectivos, con alturas promedio de 245.8 cm y 240.9 cm respectivamente, y un número considerable de flores y hojas. En conclusión, el uso de sustratos orgánicos es una alternativa viable para optimizar el cultivo de melón en invernadero, promoviendo un crecimiento saludable y sostenible.
Keywords: CUCURBITACEAS; BIOCHAR; FISIOLOGIA VEGETAL